Research on data visualisation strategies for online information dissemination based on user experience - Wei, Xiong (Applied mathematics and nonlinear sciences, 2025)
Information data visualisation is a new technology and trend emerging from the development of online information dissemination. This paper integrates the cross-field knowledge of journalism and communication, cognitive psychology and computer science, conducts two information visualisation experiments of colour symbols and cognitive load under the guidance of dual coding theory, and finds that contrasting colour schemes and symbol markers with meaningful associations help the audience’s cognition and memory of infographics. The errors caused by pie charts were much more significant than those caused by line and bar charts, and the errors caused by bar charts were much smaller than those caused by line charts. The cognitive load that pie charts cause is significantly higher than that of line and bar charts. Based on the visual representation of information visualisation, the principle of dual coding theory information processing and the results of two experiments, this paper proposes three principles of data visualisation strategy for information dissemination. This study provides theoretical support for the information visualisation design of data visualisation products, and the research conclusions and design methods can be applied to related information visualisation interfaces, which have good theoretical research value and practical significance.